Society of Vacuum Coaters : 50th Annual Technical Conference proceedings, April 28-May 3, 2007, Louisville, KY USA. (Society of Vacuum Coaters, 2007)
The Society of Vacuum Coaters is a non-profit professional and educational organization, dedicated to the development of equipment and processes for high-volume production of coatings using vacuum-based processes.